Pemberdayaan Masyarakat Desa Dalam Meningkatkan Ketahanan Pangan Melalui Teknik Hidroponik - Susda Heleni; Anisa Syafira; Ardana Ritonga; Dea Aprillia; Efni Nurlita; Iirna Andriyanti; Maya Aulia Putri; Rinaldi; Salsabila Melly Sania (Yayasan Kajian Riset Dan Pengembangan Radisi, 2022)
Hydroponics is a plant cultivation technique by utilizing a narrow area. Where this is in accordance with the conditions in Lubuk Ambacang Village, Hulu Kuantan District which is experiencing limited land for food needs. The purpose of this activity is to provide education to the Lubuk Ambacang village community regarding land use for food security using hydroponic techniques. In addition, it also aims to provide knowledge and skills to the Lubuk Ambacang village community regarding the procedures for carrying out correct hydroponic techniques. The methods used in this activity are hydroponic socialization, hydroponic demonstration, discussion and question and answer, as well as monitoring and evaluation. With education related to hydroponic socialization, it is hoped that the village community can have good knowledge of hydroponic techniques, as well as be able to apply hydroponic techniques well even with limited land. The results of the activity show that hydroponic socialization activities in Lubuk Ambacang Village can be carried out well and smoothly, which can be seen from the enthusiasm of the community in participating in hydroponic socialization activities from beginning to end, as well as growing motivation from within the community to use hydroponic techniques in farmer group activities in the village.